Gender and Visual Images: Looking Back How Stereotypes Are Presented in Textbook - Elbalqis, Putri; Wijaya, Muhammad Sayid; Rohmatillah, Rohmatillah (Universitas Islam Negeri Raden Intan Lampung, 2020)
Abstract. Gender stereotype is concerning traits and roles possessed by females and males which distinguish them from each other. It dominantly gives the ruinous impact and it possibly appears in a textbook. The objective of this research was to analyze gender stereotypes of visual images in When English Rings A Bell published in 2017. This research was in descriptive qualitative research with content analysis design, and used two components of gender schema theory – feminine and masculine traits, and feminine and masculine occupations. Documentation was applied to collect the data. To carry out the data analysis, the researcher referred to the three stages provided by Ary. The results showed that from trait aspect, generally males and females were described in common, but in two points they were showed differently; many female pictures were described with short and curly hair, and several male pictures were depicted with the bangs on their hair. Moreover, lots of females were described with darker skin, while the bright skin was described for lots of male. The occupations aspect revealed that some occupations were only described for male while the occupations; teacher, meal server, biker, hospital work, and the child care activity, were described for both of male and female. Overall, it could be said that gender stereotypes still dominantly appeared in male and female pictures. Additionally, the presentation of male and female picture showed that male pictures were being the majority, with 265 (54.75%) were male pictures, while 219 (45.25%) were female pictures, it meant that male and female were presented unequally in this textbook. Key words:gender stereotypes, gender schema theory, visual images, textbook